Assessing the assumptions: a critical analysis of agency theory - Worsham, Jeff; Ringquist, Evan J.; Eisner, Marc Allen (1997)
Principal-agent (agency) theory dominates the bureaucratic politics literature. Yet there has been very little effort devoted to assessing the assumptions of agency theory since the model was imported from economics. This article examines five major assumptions underlying agency theory. The authors suggest that the effort to translate and apply assumptions from economics to the study of bureaucratic politics misses much that is important. They offer modifications to agency theory and a new direction for research. - Reproduced
Keywords: Bureaucracy - United States; Bureaucracy